A Review on Urdhwaga Amlapitta with special reference to Hyperacidity and its Management through Vaman Karma and Dashang Kwatha. - Vahid, Abdul; Kumar, Ajay; Singhal, Tina (International Research Journal of Ayurveda & Yoga, 2023)
Amlapitta is a disease of Annavaha Srotas (Gastrointestinal tract disorder). It is caused due to improper digestion which occurred due to changing lifestyle, irregular meals timing, eating junk food and stressful behavioural pattern of people in current era., where psychological factors Play an equally important factor along with the dietary indiscretion. Signs and symptoms of Amlapitta mentioned in the Ayurvedic texts are very similar to hyperacidity. In Urdhwaga Amlpapitta vitiated Pitta and Kapha are the key factors responsible for whole pathological process. Vamana Karma is indicated as Shodhana Karma for Urdhwaga Amlapitta as well as so many formulations as Shamana Chikitsa (Dashang kwath) has mentioned in Ayurvedic Samhitas.